Genome-Wide Identification and Characterization of the LpSAPK Family Genes in Perennial Ryegrass Highlight LpSAPK9 as an Active Regulator of Drought Stress - Xing, Jing; Zhao, Ruijie; Zhang, Qing; Huang, Xinru; Yin, Tingchao; Zhang, Jing; Xu, Bin (Frontiers in Plant Science, 2022)
SAPK/SnRK2 family genes play crucial roles in plant growth, development, and abiotic stress responses. The objective of this study was to identify and characterize the LpSAPK genes in perennial ryegrass (Lolium perenne L.). The results showed that there are 10 LpSAPKs in perennial ryegrass that could be classified into three groups with similar genic (exon-intron) structures to their orthologous gens in Arabidopsis and other grass species. Ka/Ks analysis suggested that the LpSAPKs and their orthologs were under purifying selection to maintain their conserved function during evolution. Nine out of ten LpSAPKs were subcellularlly localized in cytoplasm and nucleus with the exception for LpSAPK5 that was only observed in cytoplasm. Most LpSAPKs were responsive to various abiotic stress and hormonal (ABA, cytokinin, and ethylene) treatments but were down-regulated in leaves and up-regulated in roots, suggesting that there were unknown cis-elements in promoters of these genes or unidentified post-transcriptional mechanism responsible for the tissue-dependent stress-regulated expression of these LpSAPKs. Furthermore, LpSAPK9 was identified as a candidate positive regulator in drought tolerance using a yeast ectopic expression system, and LpSAPK9 showed contrasting expression changes in drought-sensitive and -tolerant ryegrass varieties, suggesting that expression levels of LpSAPK9 were related to ryegrass drought tolerance. These results will facilitate further function analysis of LpSAPKs for molecular breeding of ryegrass and other related grass species.